Organizational communication for survival - Richmond, Virginia P. 1949- (Pearson, 2013)
This book focuses students on how to communicate with managers and peers to survive, thrive and prosper in organisational environments. It centres on understanding how and why managers communicate the way they do and how employees can adapt their own communication skills to be more effective in the organisational environment.